2009
DOI: 10.1136/bmj.b3999
|View full text |Cite|
|
Sign up to set email alerts
|

Explaining the rise in antidepressant prescribing: a descriptive study using the general practice research database

Abstract: Objective To explore the reasons behind the recent increase in antidepressant prescribing in the United Kingdom.Design Detailed retrospective analysis of data on general practitioner consultations and antidepressant prescribing. Data source Data were obtained from the general practice research database, which contains linked anonymised records of over 3 million patients registered in the UK. Data were extracted for all new incident cases of depression between 1993 and 2005.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
213
4
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(239 citation statements)
references
References 16 publications
14
213
4
2
Order By: Relevance
“…8 Data from the present study suggest better adherence to treatment than in three recent reports using comparable routine care data from England, 2 Spain, 15 and the US. 16 In contrast to at least one of these studies, 15 the present study found no clinically important difference in duration of treatment between males and females, and little difference between first-ever and subsequent treatment, suggesting a consistent approach to prescribing by GPs.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 53%
See 1 more Smart Citation
“…8 Data from the present study suggest better adherence to treatment than in three recent reports using comparable routine care data from England, 2 Spain, 15 and the US. 16 In contrast to at least one of these studies, 15 the present study found no clinically important difference in duration of treatment between males and females, and little difference between first-ever and subsequent treatment, suggesting a consistent approach to prescribing by GPs.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 53%
“…2,3 Data in this study related to all prescriptions for antidepressants commonly used to treat depression in primary care. Unlike the findings of Moore et al, 8 this research did not limit the study to patients with a computer-coded diagnosis of depression; thus the sample includes those issued an antidepressant for an anxiety disorder and those without a formally coded diagnosis.…”
Section: Comparison With Existing Literaturementioning
confidence: 78%
“…17 Similar accounts of dissonance between the medical and social model of depression have been recorded. 6,7,18,19 Research examining late-life depression suggests that patients are more comfortable accepting depression and taking antidepressants for a 'normal' chronic condition rather than a social or psychiatric condition, hence the predilection to understand the condition in physical terms. 18 Barriers to discontinuation, such as fear of withdrawal, discontinuation symptoms, and a lack of alternative treatments have been attested.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…The sample probably includes patients likely to be compliant with treatment and the rate of antidepressant prescribing (98%) is higher than that seen in other observational primary care data (80%). 15 As it is not possible to comment on the treatment of those with a single PHQ-9 measure, or draw conclusions with regard to the management of depression in patients who were not followed up, the data should not be taken to represent the global treatment of depression in primary care.…”
Section: Strengths and Limitationsmentioning
confidence: 99%